Pemasaran Produk UMKM Keripik Singkong Dan Pisang Desa Kayu Arang Kecamatan Sukaraja - Hidayatullah, Syarif; Anggraini, Ida (Jurnal Kewirausahaan & Inovasi, 2024)
This Thematic Community Service Program (KKN) aims to observe the process and marketing strategies applied in Micro, Small and Medium Enterprises (MSMEs) of cassava and banana chips production in Kayu Arang Village, Sukaraja Sub-district, Seluma Regency. The utilization of agricultural products is also designed to increase the consumption of a variety of local food sources with the principle of balanced nutrition. Business development can be directed by utilizing the potential that exists in the agricultural sector. Integrated business utilization is one of the innovations that can be used to support the economy, especially starting from the household. So that the output that you want to produce from this activity is a scientific article in the Journal of Community Service, a video of activities published on Google Drive and a Final Report in the form of a Report on the Results of the Implementation of UNIVED Thematic KKN Bengkulu Period 1. The methods used in Thematic KKN are participation, observation, interview, literature study and documentation.